PROPOSED TECHNOLOGICALMODIFICATIONS IN THE FACE OF UNCERTAINTY OF RAWMATERIALS AT THE SERGIO SOTO REFINERY - Acosta Rodríguez, Sheila María; López Bello, Nancy; Leiva Mas, Jorge; Díaz Bernal, Carlos Enrique; Bonachea Crespo, Mijail (Centro Azúcar Journal, 2025)
Introduction: The introduction of different crude oil blends into the refinery requires technological adjustments to maintain the desired quality of the dielectric oil, given its critical importance for the country. Objective: To propose technological modifications implied by variations in crude oil blends at the Sergio Soto Refinery. Materials and Methods: The characteristics of the raw material were evaluated to design a section of the atmospheric distillation plant, ensuring process quality. Results and Discussion: The technological design of the storage tanks, the partition mixer to achieve homogeneity between the crude phases, and the sizing of the pumps to ensure efficient system performance, reducing long-term operating costs, were carried out. Conclusions: The design of a partition mixer improves the homogeneity of the crude mixture and ensures better performance in the process. The proposed technological changes involve the sizing of pumps and storage tank at the outlet of the mixer. In the proposed technological solution, the investment is satisfactory, recovering in a period of three years.